If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 4 + -9 + 2 = 0 Reorder the terms: 4 + -9 + 2 + 2p = 0 Combine like terms: 4 + -9 = -5 -5 + 2 + 2p = 0 Combine like terms: -5 + 2 = -3 -3 + 2p = 0 Solving -3 + 2p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2p = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2p = 0 + 3 2p = 0 + 3 Combine like terms: 0 + 3 = 3 2p = 3 Divide each side by '2'. p = 1.5 Simplifying p = 1.5
| (5t^2-2t)-(4t+3)= | | -2+7=6-(9p+7) | | 2v-8=-12 | | 4(x-1)=x-3 | | 2p+3-4+3= | | 3d^2-17=0 | | 2p+3-4+12=3 | | Y=2*2+-3 | | -7/4y=35 | | 17=5 | | -10x(x+5)+76=-12-12 | | 2p+3-4+5= | | 10x^(1/3) | | 2p+3-4+2= | | 10x^1/3 | | -3=-5(4x+2)+21x | | 2p+3-4+1= | | 2p+3-4+10= | | 9f-1=4(2f-1)-4(-5+f) | | 2p+3-4+6= | | -4a+16+6a=7a-9a | | 2p+3-4+11= | | -3/4x-5=10 | | -6x-1=-73 | | 1/4x+3=x | | 9-2x+14=13 | | 2p+3-4+12= | | X+3.48=6.14 | | -19-(-45)=x/2 | | -5(b+8)=-7(b+2) | | 0.3x-0.7x-19=1 | | 2.6=-0.2t |